Arm race between Rift Valley fever virus and host - Wang, Xiao; Yuan, Yupei; Liu, Yihan; Zhang, Leiliang (Frontiers in Immunology, 2022)
Rift Valley fever (RVF) is a zoonotic disease caused by Rift Valley fever virus (RVFV), an emerging arbovirus within the Phenuiviridae family of Bunyavirales that has potential to cause severe diseases in both humans and livestock. It increases the incidence of abortion or foetal malformation in ruminants and leads to clinical manifestations like encephalitis or haemorrhagic fever in humans. Upon virus invasion, the innate immune system from the cell or the organism is activated to produce interferon (IFN) and prevent virus proliferation. Meanwhile, RVFV initiates countermeasures to limit antiviral responses at transcriptional and protein levels. RVFV nonstructural proteins (NSs) are the key virulent factors that not only perform immune evasion but also impact the cell replication cycle and has cytopathic effects. In this review, we summarize the innate immunity host cells employ depending on IFN signal transduction pathways, as well as the immune evasion mechanisms developed by RVFV primarily with the inhibitory activity of NSs protein. Clarifying the arms race between host innate immunity and RVFV immune evasion provides new avenues for drug target screening and offers possible solutions to current and future epidemics.